Manajemen Kepala Madrasah dalam Pembelajaran Online di Madrasah Ibtidaiyyah Negeri 3 Brebes - Arba Karomaini (Jurnal Kependidikan, 2021)
This article presents how the management of the head of MIN 3 BREBES in realizing learning effectiveness in the midst of the covid-19 pandemic situation. Problems that are clearly experienced by educational institutions at MIN 3 Brebes are the lack of knowledge and mastery of teachers regarding learning applications, as well as the strategy of the head of madrasah in conducting training on the use of google classroom. Management is a series of activities carried out to achieve the expected goals. The management of the madrasah principal occupies a strategic position so that learning continues and students do not lose their rights. This study is a qualitative research that aims to obtain an overview and information about the management of the Ibtidaiyah madrasah principal in realizing the effectiveness of learning in the midst of the covid-19 pandemic situation. The research subject is the head of the madrasa. Data were collected by means of unstructured interviews or personal discussions with the head of the madrasa as the main data source and the guardians of the students as supporting data. Data analysis was performed using data reduction techniques. The results obtained show: (1) the management of the madrasah principal has been carried out according to management rules, which include the planning, organizing and implementation stages, as well as monitoring and evaluation as steps taken so that the learning process continues to be carried out, (2) developing learning videos by making teams School IT in collecting learning videos made by MIN 3 Brebes teachers. Keywords : Management, Head of Madrasah, Covid-19 Abstrak Tulisan ini menyajikan tentang bagaimana manajemen kepala MIN 3 BREBES dalam mewujukan efektifitas pembelajaran ditengah situasi pandemi covid-19. Permasalahan yang jelas dialami lembaga pendidikan MIN 3 Brebes adalah kurangnya pengetahuan dan penguasaan guru mengenai aplikasi pembelajaran, serta straegi kepala madrasah dalam mengadakan pelatihan pemanfaatan google classroom. Manajemen merupakan serangkaian kegiatan yang dilakukan untuk mencapai tujuan yang diharapkan. Manajemen kepala madrasah menempati posisi strategis agar pembelajaran tetap terlaksana dan peserta didik tidak kehilangan haknya. Penelitian ini merupakan penelitian kualitatif yang bertujuan untuk memperoleh gambaran dan informasi tentang manajemen kepala madrasah Ibtidaiyah dalam mewujudkan efektifitas pembelajaran di tengah situasi pandemic covid-19. Subjek penelitian adalah kepala madrasah. Data dikumpulkan dengan wawancara tidak terstruktur atau diskusi personal dengnan kepala madrasah sebagai sumber data utama dan wali murid sebagai data pendukung. Analisis data dilakukan menggunakan teknik reduksi data. Hasil penelitian yang diperoleh menunjukan: (1) manajemen kepala madrasah telah dilaksanakan sebagaimana kaidah manajemen, yang meliputi tahap perencanaan, pengorganisasian dan pelaksanaan, serta pengawasan dan evaluasi sebagai langkah yang ditempuh agar proses pembelajaran tetap terlaksana, (2) mengembangkan video pembelajaran dengan membuat tim IT sekolah dalam menghimpun video pembelajaran yang dibuat oleh guru MIN 3 Brebes. Kata kunci : Manajemen, Kepala Madrasah, Covid-19